2020
DOI: 10.3390/jcm9082324
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Clinical Presentation and Incidence of Infectious Meningitis and Encephalitis in Polish Children

Abstract: Little is known about the causes and the frequency of meningitis and encephalitis in Poland. We did a retrospective single-center cohort study of children under 18 years old hospitalized with infectious meningitis or encephalitis. Incidence rates were calculated using collected data from patients from the North-East Poland only. A total of 374 children hospitalized between 1 January 2015 and 31 December 2019 were included in the study. A total of 332 (89%) children had meningitis, and 42 (11%) had encephalitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
6
1
4
Order By: Relevance
“…This finding is in accordance with a previous study that identified children and seniors as the age group with a high risk of tick bites, most probably since they have the most free time at their disposal [ 32 ]. Thus, our results do not concur with those by Toczylowski et al that reported a lower TBEV seropositivity in children compared to teenagers in Poland [ 33 ]. The differences in TBEV seroprevalence in children between the studies could be due to dissimilarities in the study design and cohort selection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in accordance with a previous study that identified children and seniors as the age group with a high risk of tick bites, most probably since they have the most free time at their disposal [ 32 ]. Thus, our results do not concur with those by Toczylowski et al that reported a lower TBEV seropositivity in children compared to teenagers in Poland [ 33 ]. The differences in TBEV seroprevalence in children between the studies could be due to dissimilarities in the study design and cohort selection.…”
Section: Discussioncontrasting
confidence: 99%
“…The differences in TBEV seroprevalence in children between the studies could be due to dissimilarities in the study design and cohort selection. Specifically, all the patients, including children, included in our study were previously exposed to tick bites; while in the study by Toczylowski et al [ 33 ] children with CNS infection of different causes including enteroviruses, varicella zoster virus, and tick-borne infections were included.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a study conducted on 374 Polish pediatric patients with CNS infection, it was observed that enteroviruses were responsible for 60% of the cases. 17 In the same study, they reported that children with proven enteroviral infection stayed in hospital shorter than children with CNS infections of other causative agents. 17 It is known that enteroviral meningitis peaks in the late summer/early autumn period, but during the pandemic period, the expected peak was not observed in autumn, as Kies et al showed in their study.…”
Section: Discussionmentioning
confidence: 93%
“…16 In a study conducted on 374 Polish pediatric patients with CNS infection, it was observed that enteroviruses were responsible for 60% of the cases. 17 In the same study, they reported that children Investigation of the Etiological Causes of Central Nervous System Infection in Children Karaaslan et al…”
Section: Discussionmentioning
confidence: 97%
“…Diagnosis can be challenging because clinical presentation of meningitis varies with age and symptoms are often nonspecific [9]. According to a study among Polish children, the most common symptoms of meningitis were headache, fever, vomiting and neck stiffness, and only 4% presented with seizures and 18% had altered level of consciousness [10]. A Swedish study investigated the differences in clinical presentation of acute bacterial meningitis in children according to age.…”
Section: Discussionmentioning
confidence: 99%